The identity of the preacher : a homiletical-critical study in Korean Presbyterian church - Kim, Kyoung-Hoan (Stellenbosch : Stellenbosch University, 2010)
Thesis (DTh (Practical Theology and Missiology))--Stellenbosch University, 2010.